Welding rod impacted in middle third of gesig: diagnosis and treatment (Research, Society and Development, 2021)
The work accident occurs through the exercise of work at the service of the company, or by the exercise of the work of the special insured, causing bodily injury or functional disturbance, of a temporary or permanent nature. These accidents represent 1.8% of the cause of facial trauma. The objective of this work is to report a case of injury by welding rod impacted on the middle third of the face after work accident, as well as the conduct employed. At the imaging examination, it was possible to observe an image compatible with a weld rod, transfixed and impacted in the middle third of the face. The protocol performed was asepsis of the face, infiltration of local anesthetic containing vasoconstrictor, removal of the impacted object with needle port, control of nasal hemorrhage with the installed anterior nasal cap and prescription of antibiotic therapy. Even though it is not the most common type of injury, maxillofacial trauma can occur in work accidents, bringing emotional consequences, the possibility of irreversible deformity and the economic impact it brings to the health system. In the case of transfixing lesions, its treatment should prioritize the stabilization of the patient, in case of successive removal of the object. Work accidents are predictable episodes that can be avoided, making it necessary for a better approach, knowing their extent and severity.